PENTINGNYA VALIDITAS DAN RELIABILITAS INSTRUMENT EVALUASI PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Derri Adi Fernando; Hartatiana Hartatiana; Fajri Ismail (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This research raises the issue of the importance of the validity and reliability of evaluation instruments in the context of Islamic Religious Education learning. Validity and reliability are important factors to ensure that evaluation instruments can measure students' understanding, values ​​and skills related to Islamic teachings accurately and consistently. The discussion includes the positive impact of validity and reliability in determining measurement accuracy, conformity with Islamic principles, measurement consistency, improving the quality of teaching and learning, trustworthiness and acceptability of evaluation results, developing effective teaching materials, and monitoring long-term progress. This research method uses descriptive qualitative through a philosophical approach to library research, using the Miles and Huberman model. By considering validity and reliability, Islamic Religious Education learning can be more effective, accurate, and in accordance with the objectives of Islamic religious education. This research provides an in-depth understanding of the important role of validity and reliability in improving the quality of Islamic Religious Education learning evaluations.